1970
DOI: 10.1159/000465904
|View full text |Cite
|
Sign up to set email alerts
|

The Recognition of Water-Soluble I Blood Group Substance

Abstract: A powerful cold auto anti-I has been found that is strongly inhibited by hydatid cyst fluid and inhibited to a varying extent by all of the 181 human saliva samples tested. The investigation showed that the inhibition effect was specific for I and that water soluble I blood group substance must be responsible. No correlation could be found between the concentration of I substance in the saliva and the presence of ABH, Lewis or Sda substances. The amount of salivary I substance secreted appears to be a constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 11 publications
1
42
0
Order By: Relevance
“…Synthesis of I antigens in different tissues has been suggested to result from different I-branching enzymes given that normal quantities of I antigen in saliva, milk, and plasma of persons with adult i phenotype has been observed. 37,38 A similar situation has been demonstrated in the formation of blood group H antigens in RBC membrane and in saliva, which are synthesized by the action of different ␣-1,2-fucosyltransferases encoded by the H and Secretor genes, respectively. 39 Whether the other I-branching enzyme encoding gene, C2GnT-M, or another unidentified gene is responsible for the I antigen expression in secretions remains to be determined.…”
Section: Discussionmentioning
confidence: 54%
“…Synthesis of I antigens in different tissues has been suggested to result from different I-branching enzymes given that normal quantities of I antigen in saliva, milk, and plasma of persons with adult i phenotype has been observed. 37,38 A similar situation has been demonstrated in the formation of blood group H antigens in RBC membrane and in saliva, which are synthesized by the action of different ␣-1,2-fucosyltransferases encoded by the H and Secretor genes, respectively. 39 Whether the other I-branching enzyme encoding gene, C2GnT-M, or another unidentified gene is responsible for the I antigen expression in secretions remains to be determined.…”
Section: Discussionmentioning
confidence: 54%
“…On the other hand, healthy quantities of I antigen have been detected in saliva, milk, and plasma of persons with the adult i phenotype of erythrocytes. 15,16 The discrepancy between blood type i and histo-blood group I antigens might have resulted from novel IGnTs, which have not cloned yet, showing a different profile of tissue distribution from conventional IGnT1. According to our own experiments of the transcript expression and the previous experimental data on the BAC clones, it is considered that 3 IGnTs are generated by alternative splicing of a single gene, sharing exons 2 and 3, which was mapped at major blood group I locus on chromosome 6.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is suggested that the discrepancy between blood group and histo-blood group I/i antigen expression can be explained by differential gene regulation of IGnT3 and the other IGnTs and C2GnT-2. 11,12,15,16 Although such gene regulation mechanism has not been examined in humans, it is noteworthy that remarkable IGnT3 gene expression is induced during erythroid differentiation of CD34 ϩ cells. The regulatory region of human IGnT3 may be different from those of IGnT1 and IGnT2 and would be in the downstream of erythropoietin signal transduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations